Biochemical‐ and Biophysical‐Induced Barriergenesis in the Blood–Brain Barrier: A Review of Barriergenic Factors for Use in In Vitro Models. Issue 5 (6th May 2021) - Schofield, Christina L.; Rodrigo-Navarro, Aleixandre; Dalby, Matthew J.; Van Agtmael, Tom; Salmeron-Sanchez, Manuel
Abstract : Blood–Brain Barrier In article number 2000068 Manuel Salmeron‐Sanchez and co‐workers invite readers to explore the Gordian Knot of blood‐brain barrier formation and maintenance. A physiological‐like model of the blood‐brain barrier would be a panacea for studying brain‐targeting drugs and diseases. Much like a forest of brain capillaries sprouting from a bed of endothelial cells, the guiding lights we find in vivo, such as key growth factors, biochemical pathways, and physical stimuli can teach us how barriergenesis may be reproduced in vitro.